Cryptorchidism as an obscure cause of adhesive small bowel obstruction in an adult, a case report. (September 2021) - Satoskar, Savni; Kashyap, Sarang; Ziehm, Joshua; Benavides, Francisco; Chang, Avian; Singhal, Vinay
Abstract: Introduction and importance: Cryptorchidism is seen in 3% of fullterm neonates. Rarely, it may cause small bowel obstruction. Knowledge of this presentation of cryptorchidism is essential to treat bowel obstruction arising due to cryptorchidism before the patient suffers complications. Case presentation: We present a case of a patient who underwent exploratory laparotomy for small bowel obstruction that did not resolve with conservative management. At laparotomy, on initial exploration, this patient had adhesive bands causing the small bowel obstruction. On further exploration, the bands were found to arise from a cryptorchid testis. Clinical discussion: Cryptorchidism is a common finding among newborns and needs to be corrected by 1 year of age. Failure to correct cryptorchidism in a timely manner can result in complications such as bowel obstruction. Conclusion: Thorough intraoperative exploration is key at operation for all cases of small bowel obstruction, so as to find and treat anatomic causes of obstruction. Congenital causes of bowel obstruction should be suspected in all unexplained cases of bowel obstruction and may be revealed by careful physical examination and thorough intraoperative exploration. Highlights: Cryptorchidism is common and requires correction by 1 year of age. Uncorrected cryptorchidism can present with complications such as bowel obstruction. Complete examination physical including the scrotum, is needed in bowel obstruction. Thorough intraoperative exploration helps find multiple points of bowel obstruction. Bowel obstruction in patients without prior surgery needs operative exploration.